(untitled) (مجلة العلوم الشاملة, 2026)
This project focuses on the design and simulation of smart building systems using the Internet of Things (IoT) and the educational software Cisco Packet Tracer, which is widely used in networking training. Unlike single-service models, the proposed system is comprehensive, integrating four key smart building services: appliance control, protection and security, garden irrigation management, and controlled building access. The system allows residents to remotely interact with their buildings through smartphones or computers from any location worldwide, enabling monitoring and control of devices in real time. A strong emphasis is placed on privacy and security, ensuring that only authorized users can manage or access building services. By combining IoT capabilities with secure communication methods, the system demonstrates an effective and educationally valuable framework for smart building simulation.